MUSIC THERAPY ON ANXIETY IN THIRD TRIMESTER PREGNANT WOMEN - Kridayanti, Novalia (Journal of Psychiatry Psychology and Behavioral Research, 2024)
Introduction – Anxiety in pregnancy poses a bad risk to the fetus. Pregnancy anxiety puts the fetus at risk for problems like delayed fetal growth. These risks can affect the quality of maternal and infant health. The use of music as therapy can be used to help overcome anxiety, especially in pregnant women. This paper will try to find out the effectiveness of listening to music as therapy against anxiety in third-trimester pregnant women. Methods – Literature obtained from Google Scholar, Elsevier, and Pubmed databases with a period of 2018 to 2023. Results – Findings from kinds of literature on the use of music therapy in managing anxiety during pregnancy are very effective in lowering anxiety levels. Discuss – Music is a non-pharmaceutical intervention that can be used as therapy. The therapeutic influence that music has on the body and mind helps balance out unpleasant feelings. Conclusion – Using music as therapy during the third trimester has beneficial effects in reducing anxiety. Therefore, the use of music therapy is expected to be used as a nonpharmacological method to reduce anxiety in pregnancy.   Keywords: music, anxiety, pregnancy.